2018
DOI: 10.1111/jth.13908
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity and the increased mortality after hospitalization for stroke: a population‐based cohort study

Abstract: Background Comorbidity is prevalent among stroke patients, affecting post-stroke survival. It remains unknown whether comorbidity impacts post-stroke mortality beyond the combined individual effects of stroke and comorbidity. Methods Using nationwide Danish databases, we performed a cohort study of 201 691 patients ≥ 18 years old with incident ischemic stroke, intracerebral or subarachnoid hemorrhage, or unspecified stroke during 1995-2012, and 992 942 adults from the general population, matched to stroke pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 31 publications
3
48
0
2
Order By: Relevance
“…Corraini et al . showed that a higher CCI score resulted in higher post-stroke mortality in patients with stroke during the first year of follow-up 43 . Schmidt et al .…”
Section: Discussionmentioning
confidence: 97%
“…Corraini et al . showed that a higher CCI score resulted in higher post-stroke mortality in patients with stroke during the first year of follow-up 43 . Schmidt et al .…”
Section: Discussionmentioning
confidence: 97%
“…increased one year mortality after stroke beyond the combined individual effects of stroke or the comorbidity 18 . Two community studies (in the United States and Spain) found that multimorbidity measured by CCI was a significant predictor of six-month mortality in stroke patients 19,20 .…”
Section: Mortalitymentioning
confidence: 98%
“…The covariates examined included age (per 5-year increase above 65), marital status (married/not married), hypertension, diabetes, COPD, history of CAD, AF, anemia, renal dysfunction (estimated glomerular filtration rate <60 mL/min/1.73 m2), time from stroke onset to rehabilitation admission <30 days, ischemic stroke, dysphagia, neglect, motor FIM score at admission, and cognitive FIM score at admission. These variables were selected based on availability at time of presentation and prior studies showing an association with the outcomes of interest (4,6,11,12,17,(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32) and were included in all analyses.…”
Section: Covariatesmentioning
confidence: 99%
“…Approximately 20-25% of stroke survivors present severe disability (3). Comorbidity is prevalent in stroke patients and affects both life expectancy and disability (4).…”
Section: Introductionmentioning
confidence: 99%